Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

First record of the entire early Sheinwoodian (Wenlock, Silurian) carbon isotope excursion (ESCIE) from Australia (eastern Gondwana) - Jiří Frýda; Stanislava Vodrážková; Barbora Frýdová; Andrew Simpson; Getie Balkie Bizunhe; David Mathieson (Palaeoworld, 2026)

Extremely heavy carbon isotope signatures of the Wenlock (Silurian) limestones in eastern Gondwana (Queensland, Australia) - Jiří Frýda; Stanislava Vodrážková; Andrew Simpson; Barbora Frýdová; David Mathieson (Palaeoworld, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Early Devonian (Lochkovian–Pragian) linguliform brachiopods from the Cobar Supergroup, western New South Wales, Australia - James L. Valentine; David K. Mathieson; Andrew J. Simpson (Palaeoworld, 2026)

Restoring a Healthier Nerve Phenotype: Mechanistic Insights into High-Concentration Capsaicin Topical System (HCCTS) for Painful Diabetic Peripheral Neuropathy (PDPN) - David M. Simpson; Samuel Allen; Audrey Carnevale; Jennifer Lohf (Toxicon, 2026)

Comparing the Impact of the High-Concentration Capsaicin Topical System (HCCTS) on Pain and Sleep in Patients With Painful Diabetic Peripheral Neuropathy (PDPN): Findings from the STEP Randomized Trial and the Real-World CASPAR Study - David M. Simpson; Samuel Allen; Audrey Carnevale; Lizandra Marcondes; Mariëlle Eerdekens (Toxicon, 2026)

Editorial: TOXINS 2026: 8th International Conference - Katharine E. Alter; Giampietro Schiavo; David Simpson (Toxicon, 2026)

Parameter-wise predictions and sensitivity analysis for random walk models in the life sciences - Yihan Liu; David J. Warne; Matthew J. Simpson (Journal of Theoretical Biology, 2026)

Long-term biomass removal in grasslands reduces plant and soil phosphorus, increases carbon:phosphorus stoichiometry, but does not lead to microbial phosphorus limitation - Andrea Simpson; David Whitehead; Leo M. Condron; Kate H. Orwin; Keith C. Cameron; Niklas J. Lehto (Agriculture, Ecosystems & Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

A phylogenetic perspective on the performance of Lactococcus lactis as starter culture in milk and plant milks - Zheng Zhao; Yuxin Zhang; David J. Simpson; Michael G. Gänzle (Food Research International, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Combining analysis of individual and wastewater whole genome sequencing improves SARS-CoV-2 surveillance - Evan P. Troendle; Andrew J. Lee; Marina I. Reyne; Danielle M. Allen; Stephen J. Bridgett; Clara H. Radulescu; Michael Glenn; John-Paul Wilkins; Francesco Rubino; Behnam Firoozi Nejad; Cormac McSparron; Marc Niebel; et al. (Water Research, 2025)

A modified scoping review of interventions for global post stroke spasticity - Areerat Suputtitada; Supattana Chatromyen; Carl PC. Chen; David M. Simpson (Toxicon, 2025)

Long chain n-alkanes in lake sediment track differences in adjacent land vegetation. - Bowen Xiao; Dënë Cheecham-Uhrich; David C. Eickmeyer; Linda E. Kimpe; Vilmantas Prėskienis; E. Henriikka Kivilä; Meiling Man; Myrna J. Simpson; Irena Creed; Milla Rautio; Jules M. Blais (Organic Geochemistry, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

An injectable oleogel-based bupivacaine formulation for prolonged non-opioid post-operative analgesia - Susan Wojtalewicz; Jack Shuckra; Keelah Barger; Sierra Erickson; Jonathon Vizmeg; Stefan Niederauer; Andrew Simpson; Jordan Davis; Avital Schauder; Orna Hifi; David Castel; Sigal Meilin; et al. (Drug Delivery and Translational Research, 2025)

Taxonomic implications of leaf anatomy in Thai Smilax (Smilacaceae) - Pornchai Kladwong; Pranom Chantaranothai; David A. Simpson (Kew Bulletin, 2025)
Summary Observations and phenetic analyses of the leaf anatomy of 23 Smilax species from Thailand were carried out to assess the utility of anatomical characters in elucidating the taxonomy of the genus. The outline of the petiole in transverse section is circular or elliptic. The abaxial outline of the midrib is rounded, acute or attenuate. Parenchymatous, sclerenchymatous and sclereid cells are observed in ground tissues. The number of vascular bundles ranged from 8 – 27 in the petioles and 2 – 11 in the midribs. The vascular bundles are surrounded by sclerenchymatous or parenchymatous cells. The mesophyll consists of 1 – 4 cell layers in the palisade part and 3 – 10 cell layers in the spongy part. Papillae are observed on the abaxial leaf surfaces of some species. Idioblast cells containing raphides are usually found in the ground tissue of the petioles, midribs and mesophylls. Epidermal cells are jigsaw-like or irregular in shape. Prismatic crystals are observed in the leaf epidermis. Stomata are anomocytic. The phenetic study was based on 11 anatomical characters using Principal Components Analysis and Discriminant Analysis to demonstrate the suitability of the classification of the studied species. Significant characteristics are the marginal outlines and the numbers of vascular bundles of the petioles, the abaxial outlines of the petioles and midribs, the numbers of cell layers of the spongy mesophyll, epidermal cell shapes and lamina types (amphistomatic or hypostomatic). The species are classified into three groups. Group I comprises three species, S. blumei , S. leucophylla and S. ovalifolia . Group II comprises 10 species, S. bracteata , S. china , S. glabra , S. luzonensis , S. microphylla , S. pertenuis , S. polyandra , S. polyacantha , S. seisuiensis and S. verticalis . Group III comprises 10 species, S. asiatica , S. calophylla , S. extensa , S. hemsleyana , S. inversa , S. lanceifolia , S. megacarpa , S. myosotiflora , S. perfoliata and S. prolifera . Descriptions of the groups and keys to the species within each group, based on the anatomical characters, are provided. Our analyses suggest that further investigation of the anatomical groups, using taxa from a broader distributional range, will be needed to clarify the relationships between the groups and the currently recognised sections.

Strain-level identification of bacteria persisting in food and in food processing facilities: when do two isolates represent the same strain and which tools identify a strain? - Vi D Pham; David J Simpson; Michael G Gänzle (Current Opinion in Food Science, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Validation and parametrization of the soil moisture index for stomatal conductance modelling and flux-based ozone risk assessment of Mediterranean plant species - Tania Carrasco-Molina; Riccardo Marzuoli; Vicent Calatayud; David Simpson; Giacomo Gerosa; Arnaud Carrara; Isaura Rábago; Rocío Alonso; Ignacio González-Fernández (Agricultural and Forest Meteorology, 2024)

Leveraging wastewater surveillance to detect viral diseases in livestock settings - Warish Ahmed; Yawen Liu; Wendy Smith; Wayne Ingall; Michael Belby; Aaron Bivins; Paul Bertsch; David T. Williams; Kirsty Richards; Stuart Simpson (Science of The Total Environment, 2024)

Bioprotective lactobacilli in Crescenza and Gouda cheese models to inhibit fungal spoilage - Zheng Zhao; David J. Simpson; Michael G. Gänzle (International Dairy Journal, 2024)

Mitogenomic evidence of population differentiation of thorny skate, Amblyraja radiata , in the North Atlantic - John S. S. Denton; Jeff Kneebone; Lei Yang; Arve Lynghammar; David McElroy; Shannon Corrigan; Klara Jakobsdóttir; Carolyn Miri; Mark Simpson; Gavin J. P. Naylor (Journal of Fish Biology, 2024)
Management of thorny skate ( Amblyraja radiata ) in the Northwest Atlantic has posed a conservation dilemma for several decades due to the species' lack of response to strong conservation efforts in the US Gulf of Maine and the Canadian Scotian Shelf, confusion over the relationship between two reproductive size morphs of differing life histories that are sympatric in the Northwest Atlantic, and conflicting data on regional population connectivity throughout the species' broader range. To better assess potential A. radiata regional population differentiation and genetic links to life‐history variation, we analysed complete mitochondrial genome sequences from 527 specimens collected across the species' North Atlantic geographic range, with particular emphasis on the Northwest Atlantic region. A high level of genetic diversity was evident across the North Atlantic, but significant genetic differentiation was identified between specimens inhabiting the Northwest (Gulf of Maine and Newfoundland) and Northeast (Greenland, Iceland, North Sea, and Arctic Circle) Atlantic. In the Northwest Atlantic, significant differentiation between the Gulf of Maine and Newfoundland regions was revealed; however, the overall level of differentiation was very low. No genetic difference was identified between the large and small reproductive morphs. The results of this study advance our understanding of A. radiata population structure in the North Atlantic but do not resolve all the questions confounding our understanding of the species' biology and evolutionary history.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Botulinum Neurotoxin Treatment Dynamics and Persistence Over 2 Years in Patients With Cervical Dystonia or Spasticity: A Retrospective Claims Database Analysis - David M. Simpson; Jonathan Bouchard; Simon Page; Dean Spurden; Seth Goldfarb; Atul T. Patel (Toxicon, 2024)

IncobotulinumtoxinA in the Treatment of Musician’s Focal Hand Dystonia: A Placebo-Controlled, Crossover Trial - David Simpson; Alexandra Nmashie; Mary Catherine George; Chuanjie Wu; Alexander Pantelyat; Eckart Altenmüller; Michael Chen; David Feng; Steven J Frucht (Toxicon, 2024)

A Phase 2b Multicenter, Randomized, Double-Blind, Placebo-Controlled Study of OnabotulinumtoxinA for the Treatment of Upper Limb Essential Tremor: ELATE Trial in Progress - Richard Barbano; David Simpson; Katelin Patterson; Nabilah Alibhai; Lynn James (Toxicon, 2024)

Acoustic backscattering at a tidal intrusion front - Christopher Bassett; Andone C. Lavery; David Ralston; W. Rockwell Geyer; Joseph T. Jurisa; Jim Thomson; David A. Honegger; Alexandra Simpson; Malcom E. Scully; Merrick C. Haller (Progress in Oceanography, 2023)

Improving toxicity prediction of metal-contaminated sediments by incorporating sediment properties - Yanfeng Zhang; Minwei Xie; David M. Spadaro; Stuart L. Simpson (Environmental Pollution, 2023)

Assessing the potential of low-transmissivity aquifers for aquifer thermal energy storage systems: a case study in Flanders (Belgium) - Luka Tas; David Simpson; Thomas Hermans (Hydrogeology Journal, 2023)
The Member States of the European Union pledged to reduce greenhouse gas emissions by 80–95% by 2050. Shallow geothermal systems might substantially contribute by providing heating and cooling in a sustainable way through seasonally storing heat and cold in the shallow ground (<200 m). When the minimum yield associated with the installation of a cost-effective aquifer thermal energy storage (ATES) system cannot be met, borehole thermal energy storage, relying mostly on the thermal conductivity of the ground, is proposed. However, for large-scale applications, this requires the installation of hundreds of boreholes, which entails a large cost and high disturbance of the underground. In such cases, ATES systems can nevertheless become interesting. This paper presents a case study performed on a Ghent University campus (Belgium), where the feasibility of ATES in an area with a low transmissivity was determined. The maximum yield of the aquifer was estimated at 5 m 3 /h through pumping tests. Although this low yield was attributed to the fine grain size of the aquifer, membrane filtering index tests and long-term injection tests revealed that the clogging risk was limited. A groundwater model was used to optimize the well placement. It was shown that a well arrangement in a checkerboard pattern was most effective to optimize the hydraulic efficiency while maintaining the thermal recovery efficiency of the ATES system. Hence, for large-scale projects, efficient thermal energy storage can also be achieved using a (more cost-effective) ATES system even in low-permeability sediments.

Integrated Exposure–Response of Dupilumab in Children, Adolescents, and Adults With Atopic Dermatitis Using Categorical and Continuous Efficacy Assessments: A Population Analysis - Emily Briggs; Mohamed A. Kamal; Matthew P. Kosloski; Ian Linsmeier; Natalie Jusko; Nancy Dolphin; Jason Chittenden; Eric L. Simpson; Amy S. Paller; Elaine C. Siegfried; Brad Shumel; Noah A. Levit; et al. (Pharmaceutical Research, 2023)
Background While the majority of patients with atopic dermatitis (AD) achieve disease control with dupilumab treatment, there is variability in which patients achieve clear disease. The predictors of these responses are currently unclear. Integrated models were developed to evaluate the exposure–response (E-R) relationship of dupilumab in children, adolescents, and adults with AD. Methods Data from six Phase II and III clinical studies were pooled (2,366 adults [> 18 years], 243 adolescents [≥ 12 to < 18 years] and 359 children [≥ 6 to < 12 years]) for model development. Efficacy was assessed using the Eczema Area and Severity Index (EASI) and Investigator’s Global Assessment (IGA). Indirect response models were applied to link measures of efficacy and functional serum dupilumab concentrations. The covariates on individual placebo-corrected response were assessed. Clinical trial scenarios were simulated to compare E-R relationships across age groups. Safety was not explored. Results After correcting for differences in placebo response and dupilumab exposure: 1) older age, higher body weight, lower baseline thymus and activation-regulated chemokine, and Asian race were associated with slightly lower EASI response, and no clear covariates were identified on IGA response; 2) clinical trial simulations generally showed slightly higher response at a given dupilumab concentration in children compared to adults and adolescents with severe and moderate AD. Conclusions The collectively tested covariates explain some of the variability in dupilumab response in patients with AD. Patients in all age groups showed adequate response to dupilumab; however, children showed slightly higher drug effects compared to adults and adolescents at equivalent concentrations.

Apatite laser ablation Lu Hf geochronology: A new tool to date mafic rocks - Melissa B.K. Kharkongor; Stijn Glorie; Jacob Mulder; Christopher L. Kirkland; David Chew; Barry Kohn; Alexander Simpson (Chemical Geology, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Canada and ocean climate adaptation: tracking law and policy responses, charting future directions - David L. VanderZwaag; Sara L. Seck; Laura Graham; Jonathon Frontain; Kieran Simpson (Frontiers in Marine Science, 2023)
This research article provides a law and policy summary of climate change adaptation initiatives in Canada at the ocean-climate nexus. Three levels of governance are examined (national, provincial, and Indigenous) with a focus on the Atlantic region. The research method was the review of relevant and newly amended laws, regulations and policy statements, and related commentaries. The roles of the federal government are first described with key developments including the launch of a Climate Adaptation Platform in 2012 to share adaptation experiences and information and release of a National Adaptation Strategy and accompanying Adaptation Action Plan in November 2022. Federal adaptation efforts in the areas of fisheries, aquaculture and shipping are also reviewed along with progress in establishing marine protected areas (MPAs) and other effective area-based conservation measures. Provincial adaptation initiatives are next summarized with a focus on the four Atlantic provinces. Those provinces have established a regional hub, CLIMAtlantic, to provide climate information and advance climate-related research and training. Each province has developed a climate action plan which includes climate adaptation priorities. Indigenous-led climate engagement and adaptation initiatives are finally described including the publication in 2019 of a National Inuit Climate Change Strategy , regional initiatives of the Atlantic Policy Congress of First Nations Chiefs Secretariat, and the development of climate adaptation plans by select First Nation communities in the Atlantic region. The paper concludes by discussing future law and policy directions to make Canada more “climate ready.” Adoption of climate adaptation strategies for governmental departments and agencies with ocean and coastal responsibilities should be a priority. Incorporating climate change adaptation responsibilities through legislative and regulatory changes also needs to be considered, for example, by amending Canada’s Oceans Act to recognize the role of oceans in climate adaptations and mitigation, to authorize the designation of MPAs as climate refuges and to require adaptive and dynamic MPA management plans through strict monitoring and timely review provisions. Indigenous peoples must be effectively included in all climate adaptation discussions and planning.

Geochemical and physical variability of Icelandic tephra fields and glaciovolcanic sandur to inform spatial sampling in Mars biosignature searches - Morgan L. Cable; Alexander M. Sessa; Erika Rader; Anna C. Simpson; Ashley M. Hanna; Diana M. Gentry; Scot M. Sutton; Elena S. Amador; Carlie Novak; Chloe LeCates; Mark Helmlinger; Amanda M. Stockton; et al. (Planetary and Space Science, 2023)

Deficiency of the mitochondrial ribosomal subunit, MRPL50, causes autosomal recessive syndromic premature ovarian insufficiency - Shabnam Bakhshalizadeh; Daniella H. Hock; Nicole A. Siddall; Brianna L. Kline; Rajini Sreenivasan; Katrina M. Bell; Franca Casagranda; Sadishkumar Kamalanathan; Jayaprakash Sahoo; Niya Narayanan; Dukhabandhu Naik; Varun Suryadevara; et al. (Human Genetics, 2023)
Premature ovarian insufficiency (POI) is a common cause of infertility in women, characterised by amenorrhea and elevated FSH under the age of 40 years. In some cases, POI is syndromic in association with other features such as sensorineural hearing loss in Perrault syndrome. POI is a heterogeneous disease with over 80 causative genes known so far; however, these explain only a minority of cases. Using whole-exome sequencing (WES), we identified a MRPL50 homozygous missense variant (c.335T > A; p.Val112Asp) shared by twin sisters presenting with POI, bilateral high-frequency sensorineural hearing loss, kidney and heart dysfunction. MRPL50 encodes a component of the large subunit of the mitochondrial ribosome. Using quantitative proteomics and western blot analysis on patient fibroblasts, we demonstrated a loss of MRPL50 protein and an associated destabilisation of the large subunit of the mitochondrial ribosome whilst the small subunit was preserved. The mitochondrial ribosome is responsible for the translation of subunits of the mitochondrial oxidative phosphorylation machinery, and we found patient fibroblasts have a mild but significant decrease in the abundance of mitochondrial complex I. These data support a biochemical phenotype associated with MRPL50 variants. We validated the association of MRPL50 with the clinical phenotype by knockdown/knockout of mRpL50 in Drosophila , which resulted abnormal ovarian development. In conclusion, we have shown that a MRPL50 missense variant destabilises the mitochondrial ribosome, leading to oxidative phosphorylation deficiency and syndromic POI, highlighting the importance of mitochondrial support in ovarian development and function.

Usability of existing global and national data for flood related vulnerability assessment in Indonesia - Breanne K. Langlois; Elizabeth Marsh; Tyler Stotland; Ryan B. Simpson; Katherine Berry; David A. Carroll; Aris Ismanto; Magaly Koch; Elena N. Naumova (Science of The Total Environment, 2023)

Genome screening, reporting, and genetic counseling for healthy populations - Selina Casalino; Erika Frangione; Monica Chung; Georgia MacDonald; Sunakshi Chowdhary; Chloe Mighton; Hanna Faghfoury; Yvonne Bombard; Lisa Strug; Trevor J. Pugh; Jared Simpson; Saranya Arnoldo; et al. (Human Genetics, 2023)

Effects of interactions between anthropogenic stressors and recurring perturbations on ecosystem resilience and collapse - David A. Keith; Doug H. Benson; Ian R. C. Baird; Laura Watts; Christopher C. Simpson; Martin Krogh; Sarsha Gorissen; Jose R. Ferrer‐Paris; Tanya J. Mason (Conservation Biology, 2023)
Insights into declines in ecosystem resilience and their causes and effects can inform preemptive action to avoid ecosystem collapse and loss of biodiversity, ecosystem services, and human well‐being. Empirical studies of ecosystem collapse are rare and hampered by ecosystem complexity, nonlinear and lagged responses, and interactions across scales. We investigated how an anthropogenic stressor could diminish ecosystem resilience to a recurring perturbation by altering a critical ecosystem driver. We studied groundwater‐dependent, peat‐accumulating, fire‐prone wetlands known as upland swamps in southeastern Australia. We hypothesized that underground mining (stressor) reduces resilience of these wetlands to landscape fires (perturbation) by diminishing groundwater, a key ecosystem driver. We monitored soil moisture as an indicator of ecosystem resilience during and after underground mining. After landscape fire, we compared responses of multiple state variables representing ecosystem structure, composition, and function in swamps within the mining footprint with unmined reference swamps. Soil moisture declined without recovery in swamps with mine subsidence (i.e., undermined), but was maintained in reference swamps over 8 years (effect size 1.8). Relative to burned reference swamps, burned undermined swamps showed greater loss of peat via substrate combustion; reduced cover, height, and biomass of regenerating vegetation; reduced postfire plant species richness and abundance; altered plant species composition; increased mortality rates of woody plants; reduced postfire seedling recruitment; and extirpation of a hydrophilic animal. Undermined swamps therefore showed strong symptoms of postfire ecosystem collapse, whereas reference swamps regenerated vigorously. We found that an anthropogenic stressor diminished the resilience of an ecosystem to recurring perturbations, predisposing it to collapse. Avoidance of ecosystem collapse hinges on early diagnosis of mechanisms and preventative risk reduction. It may be possible to delay or ameliorate symptoms of collapse or to restore resilience, but the latter appears unlikely in our study system due to fundamental alteration of a critical ecosystem driver. Efectos de las interacciones entre los estresantes antropogénicos y las perturbaciones recurrentes sobre la resiliencia y el colapso de los ecosistemas

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Modelling the effects of cold temperature during the reproductive stage on the yield of chickpea (Cicer arietinum L.) - Muhuddin Rajin Anwar; David J. Luckett; Yashvir S. Chauhan; Ryan H. L. Ip; Lancelot Maphosa; Marja Simpson; Annie Warren; Rosy Raman; Mark F. Richards; Georgina Pengilley; Kristy Hobson; Neroli Graham (International Journal of Biometeorology, 2022)
During the reproductive stage, chilling temperatures and frost reduce the yield of chickpea and limit its adaptation. The adverse effects of chilling temperature and frost in terms of the threshold temperatures, impact of cold duration, and genotype-by-environment-by-management interactions are not well quantified. Crop growth models that predict flowering time and yield under diverse climates can identify combinations of cultivars and sowing time to reduce frost risk in target environments. The Agricultural Production Systems Simulator (APSIM-chickpea) model uses daily temperatures to model basic crop growth but does not include penalties for either frost damage or cold temperatures during flowering and podding stages. Regression analysis overcame this limitation of the model for chickpea crops grown at 95 locations in Australia using 70 years of historic data incorporating three cultivars and three sowing times (early, mid, and late). We modified model parameters to include the effect of soil water on thermal time calculations, which significantly improved the prediction of flowering time. Simulated data, and data from field experiments grown in Australia (2013 to 2019), showed robust predictions for flowering time ( n = 29; R 2 = 0.97), and grain yield ( n = 22; R 2 = 0.63–0.70). In addition, we identified threshold cold temperatures that significantly affected predicted yield, and combinations of locations, variety, and sowing time where the overlap between peak cold temperatures and peak flowering was minimal. Our results showed that frost and/or cold temperature–induced yield losses are a major limitation in some unexpected Australian locations, e.g., inland, subtropical latitudes in Queensland. Intermediate sowing maximise yield, as it avoids cold temperature, late heat, and drought stresses potentially limiting yield in early and late sowing respectively.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Biomarkers in Ringed Seals Reveal Recent Onset of Borealization in the High- Compared to the Mid-Latitude Canadian Arctic - Camille de la Vega; Claire Mahaffey; David J. Yurkowski; Louisa Norman; Elysia Simpson; Sophie Smout; Steven H. Ferguson; Rachel M. Jeffreys (Frontiers in Marine Science, 2021)
Warming of the Arctic has resulted in environmental and ecological changes, termed borealization, leading to the northward shift of temperate species. Borealization has occurred across all trophic levels, altering the structure of the food web. The onset and rate of borealization likely varies with latitude, depending on local warming and advection of warmer water into the Arctic. In order to assess latitudinal trends in food web structure in the Arctic, we analyzed stable nitrogen isotopes of specific amino acids alongside bulk stable carbon isotopes in ringed seal muscle tissue from the Canadian Arctic Archipelago (high-Arctic) and Southern Baffin Bay (mid-Arctic) from 1990 to 2016. Our results indicate a shift in food web structure in the high-Arctic that has occurred more recently when compared with the mid-Arctic. Specifically, over the past 25 years, the trophic position of ringed seals from the mid-Arctic was largely constant, whereas the trophic position of ringed seals decreased in the high-Arctic, reaching similar values observed in the mid-Arctic in 2015–2016. This suggests a potential shortening of the food chain length in the high-Arctic, possibly driven by changes in zooplankton communities feeding complexity in association with sea ice decline. This study identifies a temporal offset in the timing of borealization in the Canadian Arctic, resulting in different response of food webs to ecological changes, depending on latitude.

Summary of East Gondwanan Conodont Data through the Ireviken Event at Boree Creek - Andrew Simpson; David Mathieson; Jiri Frýda; Barbora Frýdová (Journal of Earth Science, 2021)

Multichannel search strategy for improving the detection of auditory steady-state response - Felipe Antunes; Tiago Zanotelli; David Martin Simpson; Leonardo Bonato Felix (Medical & Biological Engineering & Computing, 2021)

Microbial fuel cell biosensor for the determination of biochemical oxygen demand of wastewater samples containing readily and slowly biodegradable organics - Gábor Márk Tardy; Bálint Lóránt; Miklós Gyalai-Korpos; Vince Bakos; David Simpson; Igor Goryanin (Biotechnology Letters, 2021)
Objectives Single-chamber air cathode microbial fuel cells (MFCs) were applied as biosensors for biochemical oxygen demand (BOD) measurement of real wastewaters with considerable suspended and/or slowly biodegradable organic content. Results The measurement method consists of batch sample injection, continuous measurement of cell voltage and calculation of total charge (Q) gained during the biodegradation of organic content. Diverse samples were analyzed: acetate and peptone samples containing only soluble readily biodegradable substrates; corn starch and milk samples with suspended and colloidal organics; real domestic and brewery wastewaters. Linear regression fitted to the Q vs. BOD 5 measurement points of the real wastewaters provided high (> 0.985) R 2 values. Time requirement of the measurement varied from 1 to 4 days, depending on the composition of the sample. Conclusions Relative error of BOD measured in the MFCs comparing with BOD 5 was less than 10%, thus the method might be a good basis for the development of on-site automatic BOD sensors for real wastewater samples.

Historical overview and new directions in bioarchaeological trace element analysis: a review - Rachel Simpson; David M. L. Cooper; Treena Swanston; Ian Coulthard; Tamara L. Varney (Archaeological and Anthropological Sciences, 2021)
Given their strong affinity for the skeleton, trace elements are often stored in bones and teeth long term. Diet, geography, health, disease, social status, activity, and occupation are some factors which may cause differential exposure to, and uptake of, trace elements, theoretically introducing variability in their concentrations and/or ratios in the skeleton. Trace element analysis of bioarchaeological remains has the potential, therefore, to provide rich insights into past human lifeways. This review provides a historical overview of bioarchaeological trace element analysis and comments on the current state of the discipline by highlighting approaches with growing momentum. Popularity for the discipline surged following preliminary studies in the 1960s to 1970s that demonstrated the utility of strontium (Sr) as a dietary indicator. During the 1980s, Sr/Ca ratio and multi-element studies were commonplace in bioarchaeology, linking trace elements with dietary phenomena. Interest in using trace elements for bioarchaeological inferences waned following a period of critiques in the late 1980s to 1990s that argued the discipline failed to account for diagenesis, simplified complex element uptake and regulation processes, and used several unsuitable elements for palaeodietary reconstruction (e.g. those under homeostatic regulation, those without a strong affinity for the skeleton). In the twenty-first century, trace element analyses have been primarily restricted to Sr and lead (Pb) isotope analysis and the study of toxic trace elements, though small pockets of bioarchaeology have continued to analyse multiple elements. Techniques such as micro-sampling, element mapping, and non-traditional stable isotope analysis have provided novel insights which hold the promise of helping to overcome limitations faced by the discipline.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Genomic sequencing highlights the diverse molecular causes of Perrault syndrome: a peroxisomal disorder (PEX6), metabolic disorders (CLPP, GGPS1), and mtDNA maintenance/translation disorders (LARS2, TFAM) - Elena J. Tucker; Rocio Rius; Sylvie Jaillard; Katrina Bell; Phillipa J. Lamont; André Travessa; Juliette Dupont; Lurdes Sampaio; Jérôme Dulon; Sandrine Vuillaumier-Barrot; Sandra Whalen; Arnaud Isapof; et al. (Human Genetics, 2020)

Architectural Geoheritage, Engaging the Observer and the Geotourism Potential of the Lighthouse Hotel Rock Wall, Bunbury, Western Australia - Samantha J. Richards; David Newsome; Greg Simpson (Geoheritage, 2020)

Identifying archaeological evidence of past earthquakes in a contemporary disaster scenario: case studies of damage, resilience and risk reduction from the 2015 Gorkha Earthquake and past seismic events within the Kathmandu Valley UNESCO World Heritage Property (Nepal) - Christopher Davis; Robin Coningham; Kosh Prasad Acharya; Ram Bahadur Kunwar; Paolo Forlin; Kai Weise; Prem Nath Maskey; Anie Joshi; Ian Simpson; David Toll; Sean Wilkinson; Paul Hughes; et al. (Journal of Seismology, 2020)
The 2015 Gorkha Earthquake was a humanitarian disaster but also a cultural catastrophe that damaged and destroyed historic monuments across Nepal, including those within the Kathmandu Valley UNESCO World Heritage Property. In the rush to rebuild, traditionally constructed foundations are being removed and replaced with modern materials without assessments of whether these contributed to the collapse of a monument. Generally undertaken without scientific recording, these interventions have led to the irreversible destruction of earlier subsurface phases of cultural activity and the potential loss of evidence for successful traditional seismic adaptations and risk reduction strategies, with no research into whether modern materials, such as concrete and steel, would offer enhanced resilience. In response to this context, multidisciplinary post-disaster investigations were undertaken between 2015 and 2018, including archaeological excavation, geophysical survey, geoarchaeological analysis, linked to architectural and engineering studies, to begin to evaluate and assess the damage to, and seismic adaptations of, historic structures within Nepal’s Kathmandu Valley. Where possible, we draw on archaeoseismological approaches for the identification and classification of Earthquake Archaeological Effects (EAEs) at selected monuments damaged by the 2015 Gorkha Earthquake. Lessons learned from evidence of potential weaknesses, as well as historic ‘risk-sensitive tactics’ of hazard reduction within monuments, are now being incorporated into reconstruction and rehabilitation initiatives alongside the development of methods for the protection of heritage in the face of future earthquakes.

Design of a Drug-Eluting Subcutaneous Implant of the Antiretroviral Tenofovir Alafenamide Fumarate - Solange M Simpson; Lakmini Widanapathirana; Jonathan T. Su; Samuel Sung; David Watrous; Jiang Qiu; Elizabeth Pearson; Alex Evanoff; Dipu Karunakaran; Jorge E. Chacon; Patrick F. Kiser (Pharmaceutical Research, 2020)
Purpose Sexual transmission of HIV has been clinically proven to be preventable with a once-daily oral tablet; however, missed doses dramatically increase the risk of HIV infection. Long-acting subcutaneous implants do not allow the user to miss a dose. A desirable long-acting drug-eluting implant can deliver a constant amount of drug, adjust the delivered dose, and be readily manufactured. We present a long-acting, subcutaneous implant design composed of tenofovir alafenamide hemifumarate (TAF) pellets loaded in a sealed polyether urethane tube for the prevention of HIV transmission. Methods Implants were prepared with pressed drug pellets and extruded polyurethane tubing. In vitro release rate of implants using different pellet formulations, rate-controlling membranes, and geometries were measured. Results Tenofovir alafenamide release appeared to be governed by a pseudo-steady state and followed a mass transport model of release from a cylindrical drug reservoir. Implant seal integrity was tested and confirmed using mechanical testing. The inclusion of sodium chloride in the pellet increased the release rate and reduced initial lag. The release was sustained for 100 days. Conclusions The release rate of tenofovir alafenamide mechanistically varied with geometry and rate controlling membrane composition. The polyether urethane implant presented herein is modular and tunable to adjust the release rate and duration of the TAF release.

Epichloe novae‐zelandiae , a new endophyte from the endemic New Zealand grass Poa matthewsii - Adrian Leuchtmann; Carolyn A. Young; Alan V. Stewart; Wayne R. Simpson; David E. Hume; Barry Scott (New Zealand Journal of Botany, 2019)
Epichloe endophytes (Clavicipitaceae) infect pooid grass genera worldwide but predominantly in the Northern Hemisphere, but appear to be rare in native grasses of the Southern Hemisphere. Because of benefits that hosts may receive from the symbiosis, Epichloe endophytes have been extensively studied and are considered important components of sustainable agriculture. There are only a few studies available on the incidence of endophyte infection in grasses of the Southern Hemisphere and most grass species have never been examined. Here we report on a survey of native grasses of New Zealand including 25 endemic or indigenous species. We sampled up to 10 plants per species at different sites from both the North and South Island of New Zealand and examined tissues microscopically for endophyte infection. Overall, only two species were found to be infected, Poa matthewsii (Matthew's bluegrass) and Dichelachne micrantha (short‐hair plume grass). Based on analyses of tefA and tubB genes, both endophytes were found to be interspecific hybrids. The endophyte of the new host D. micrantha was previously described as Epichloe australiensis , while the endophyte of P. matthewsii is a new species named here E. novae‐zelandiae . The new species is a hybrid derived from E. amarillans , E. bromicola and E. typhina subsp. poae. Alkaloid analyses in planta suggested that E. novae‐zelandiae can produce small amounts of peramine, early pathway indole‐diterpenes and ergot alkaloids, but no lolines or lolitrems. Target specific primers suggested the presence of genes for ergot alkaloids and peramine, but genes of only early pathway steps for the other alkaloids. Furthermore, genes for both mating type idiomorphs ( MTA and MTB ) were present, a single copy of MTA and two copies of MTB . Endophytes of native grasses may provide a genetic resource that could be exploited for developing pasture grass cultivars with improved performance.

Coral Reef Monitoring, Reef Assessment Technologies, and Ecosystem-Based Management - David O. Obura; Greta Aeby; Natchanon Amornthammarong; Ward Appeltans; Nicholas Bax; Joe Bishop; Russell E. Brainard; Samuel Chan; Pamela Fletcher; Timothy A. C. Gordon; Lew Gramer; Mishal Gudka; et al. (Frontiers in Marine Science, 2019)

Two new species of Justicia (Acanthaceae) from northern Thailand - Kanokorn Rueangsawang; Pranom Chantaranothai; David A. Simpson (Kew Bulletin, 2019)
Summary Two new species, Justicia flavescens and J. vasculosoides are described and illustrated from northern Thailand. Both species have restricted distributions. The conservation status of each species is assessed.

The endangered White's seahorse Hippocampus whitei chooses artificial over natural habitats - Michael Simpson; Rebecca L. Morris; David Harasti; Ross A. Coleman (Journal of Fish Biology, 2019)
To explore whether the endangered White's seahorse Hippocampus whitei would choose to inhabit artificial over natural habitats, 10 adult H. whitei individuals were put through a series of binary choice trials in aquaria, during which they were offered different paired combinations of natural (different types of macroalga and seagrass) and artificial habitat (panels of swimming‐net material). It was found that H. whitei displayed a significant choice for swimming‐net material over all other available natural habitats and chose habitats according to the following rankings: (a) Net; (b) Sargassum sp.; (c) Posidonia australis ; (d) Zostera muelleri. Hippocampus whitei ’s choice of swimming net material over natural habitat suggests that these artificial structures could be a useful conservation measure for seahorses in areas where natural habitat is becoming less favourable due to declines in abundance or quality.

Impacts of tropospheric ozone and climate change on Mexico wheat production - Jose Rafael Guarin; Lisa Emberson; David Simpson; Ixchel M. Hernandez-Ochoa; Diane Rowland; Senthold Asseng (Climatic Change, 2019)

Subject-Specific Surgical Planning for Hip Replacement: A Novel 2D Graphical Representation of 3D Hip Motion and Prosthetic Impingement Information - Arnab Palit; Richard King; Yolanda Gu; James Pierrepont; David Simpson; Mark A. Williams (Annals of Biomedical Engineering, 2019)

Melt segregation and the architecture of magmatic reservoirs: insights from the Muroto sill (Japan) - David Floess; Luca Caricchi; Guy Simpson; Simon R. Wallis (Contributions to Mineralogy and Petrology, 2019)

White matter damage, neuroinflammation, and neuronal integrity in HAND - Aljoharah Alakkas; Ronald J. Ellis; Caitlin Wei-Ming Watson; Anya Umlauf; Robert K. Heaton; Scott Letendre; Ann Collier; Christina Marra; David B. Clifford; Benjamin Gelman; Ned Sacktor; Susan Morgello; et al. (Journal of NeuroVirology, 2019)

Physical and chemical impacts of a major storm on a temperate lake: a taste of things to come? - R. Iestyn Woolway; John H. Simpson; David Spiby; Heidrun Feuchtmayr; Ben Powell; Stephen C. Maberly (Climatic Change, 2018)

Closing the global ozone yield gap: Quantification and cobenefits for multistress tolerance - Gina Mills; Katrina Sharps; David Simpson; Håkan Pleijel; Michael Frei; Kent Burkey; Lisa Emberson; Johan Uddling; Malin Broberg; Zhaozhong Feng; Kazuhiko Kobayashi; Madhoolika Agrawal (Global Change Biology, 2018)
Increasing both crop productivity and the tolerance of crops to abiotic and biotic stresses is a major challenge for global food security in our rapidly changing climate. For the first time, we show how the spatial variation and severity of tropospheric ozone effects on yield compare with effects of other stresses on a global scale, and discuss mitigating actions against the negative effects of ozone. We show that the sensitivity to ozone declines in the order soybean > wheat > maize > rice, with genotypic variation in response being most pronounced for soybean and rice. Based on stomatal uptake, we estimate that ozone (mean of 2010–2012) reduces global yield annually by 12.4%, 7.1%, 4.4% and 6.1% for soybean, wheat, rice and maize, respectively (the “ozone yield gaps”), adding up to 227 Tg of lost yield. Our modelling shows that the highest ozone‐induced production losses for soybean are in North and South America whilst for wheat they are in India and China, for rice in parts of India, Bangladesh, China and Indonesia, and for maize in China and the United States. Crucially, we also show that the same areas are often also at risk of high losses from pests and diseases, heat stress and to a lesser extent aridity and nutrient stress. In a solution‐focussed analysis of these results, we provide a crop ideotype with tolerance of multiple stresses (including ozone) and describe how ozone effects could be included in crop breeding programmes. We also discuss altered crop management approaches that could be applied to reduce ozone impacts in the shorter term. Given the severity of ozone effects on staple food crops in areas of the world that are also challenged by other stresses, we recommend increased attention to the benefits that could be gained from addressing the ozone yield gap.

Identification of powdery mildew resistance QTL in strawberry (Fragaria × ananassa) - Helen M. Cockerton; Robert J. Vickerstaff; Amanda Karlström; Fiona Wilson; Maria Sobczyk; Joe Q. He; Daniel J. Sargent; Andy J. Passey; Kirsty J. McLeary; Katalin Pakozdi; Nicola Harrison; Maria Lumbreras-Martinez; et al. (Theoretical and Applied Genetics, 2018)

Ozone pollution will compromise efforts to increase global wheat production - Gina Mills; Katrina Sharps; David Simpson; Håkan Pleijel; Malin Broberg; Johan Uddling; Fernando Jaramillo; William J Davies; Frank Dentener; Maurits Van den Berg; Madhoolika Agrawal; Shahibhushan B. Agrawal; et al. (Global Change Biology, 2018)
Introduction of high‐performing crop cultivars and crop/soil water management practices that increase the stomatal uptake of carbon dioxide and photosynthesis will be instrumental in realizing the United Nations Sustainable Development Goal ( SDG ) of achieving food security. To date, however, global assessments of how to increase crop yield have failed to consider the negative effects of tropospheric ozone, a gaseous pollutant that enters the leaf stomatal pores of plants along with carbon dioxide, and is increasing in concentration globally, particularly in rapidly developing countries. Earlier studies have simply estimated that the largest effects are in the areas with the highest ozone concentrations. Using a modelling method that accounts for the effects of soil moisture deficit and meteorological factors on the stomatal uptake of ozone, we show for the first time that ozone impacts on wheat yield are particularly large in humid rain‐fed and irrigated areas of major wheat‐producing countries (e.g. United States, France, India, China and Russia). Averaged over 2010–2012, we estimate that ozone reduces wheat yields by a mean 9.9% in the northern hemisphere and 6.2% in the southern hemisphere, corresponding to some 85 Tg (million tonnes) of lost grain. Total production losses in developing countries receiving Official Development Assistance are 50% higher than those in developed countries, potentially reducing the possibility of achieving UN SDG 2. Crucially, our analysis shows that ozone could reduce the potential yield benefits of increasing irrigation usage in response to climate change because added irrigation increases the uptake and subsequent negative effects of the pollutant. We show that mitigation of air pollution in a changing climate could play a vital role in achieving the above‐mentioned UN SDG , while also contributing to other SDG s related to human health and well‐being, ecosystems and climate change.

Environmental exposure and parental collection does not affect detection or semi-quantitative load assessment of bacteria in nasal swab specimens from children - Nada Townsi; Shannon J. Simpson; Chisha T. Sikazwe; Glenys R. Chidlow; Graham L. Hall; J. Jane Pillow; Andrew C. Wilson; David W. Smith; Ingrid A. Laing (Infectious Diseases, 2018)

Nomenclatural notes on the family Smilacaceae in Thailand - Pornchai Kladwong; Pranom Chantaranothai; David A. Simpson (Kew Bulletin, 2018)

Safety, tolerability and pharmacokinetics of GSK3008348, a novel integrin αvβ6 inhibitor, in healthy participants - Charlotte H. Maden; David Fairman; Michelle Chalker; Maria J. Costa; William A. Fahy; Nadia Garman; Pauline T. Lukey; Tim Mant; Simon Parry; Juliet K. Simpson; Robert J. Slack; Stuart Kendrick; et al. (European Journal of Clinical Pharmacology, 2018)

Notes on the taxonomy and lectotypification of Cyperus macer (Cyperaceae) - V. P. Prasad; David A. Simpson (Kew Bulletin, 2017)

Predictive control of intersegmental tarsal movements in an insect - Alicia Costalago-Meruelo; David M. Simpson; Sandor M. Veres; Philip L. Newland (Journal of Computational Neuroscience, 2017)

Ilex pubifructa (Aquifoliaceae), a new species from northern Thailand - Kanchana Pruesapan; Susyn Andrews; David A. Simpson (Kew Bulletin, 2017)

Evaluating the accuracy of self-report for the diagnosis of HIV-associated neurocognitive disorder (HAND): defining “symptomatic” versus “asymptomatic” HAND - Lisa C. Obermeit; Jessica Beltran; Kaitlin B. Casaletto; Donald R. Franklin; Scott Letendre; Ronald Ellis; Christine Fennema-Notestine; Florin Vaida; Ann C. Collier; Christina M. Marra; David Clifford; Benjamin Gelman; et al. (Journal of NeuroVirology, 2017)

Analysis of compound heterozygotes reveals that the mouse floxed Pax6 tm1Ued allele produces abnormal eye phenotypes - Natalie J. Dorà; Aaron J. F. Crookshanks; Karen K. Y. Leung; T. Ian Simpson; John O. Mason; David J. Price; John D. West (Transgenic Research, 2016)

Apolipoprotein E ε4 genotype status is not associated with neuroimaging outcomes in a large cohort of HIV+ individuals - Sarah A. Cooley; Robert H. Paul; Christine Fennema-Notestine; Erin E. Morgan; Florin Vaida; Qianqian Deng; Jie Ashley Chen; Scott Letendre; Ronald Ellis; David B. Clifford; Christina M. Marra; Ann C. Collier; et al. (Journal of NeuroVirology, 2016)

Comment on ‘Anav et al . (2016) Comparing concentration‐based (AOT40) and stomatal uptake (PODY) metrics for ozone risk assessment to European forests’ Global Change Biology, 22(4), 1608–1627, doi:10.1111/gcb.13138 - David Simpson (Global Change Biology, 2016)

Persistent CSF but not plasma HIV RNA is associated with increased risk of new-onset moderate-to-severe depressive symptoms; a prospective cohort study - Edward R. Hammond; Rosa M. Crum; Glenn J. Treisman; Shruti H. Mehta; David B. Clifford; Ronald J. Ellis; Benjamin B. Gelman; Igor Grant; Scott L. Letendre; Christina M. Marra; Susan Morgello; David M. Simpson; et al. (Journal of NeuroVirology, 2016)

NiftyFit: a Software Package for Multi-parametric Model-Fitting of 4D Magnetic Resonance Imaging Data - Andrew Melbourne; Nicolas Toussaint; David Owen; Ivor Simpson; Thanasis Anthopoulos; Enrico De Vita; David Atkinson; Sebastien Ourselin (Neuroinformatics, 2016)

Typification of the African endemic plant Ottelia exserta (Hydrocharitaceae) - P. Pablo Ferrer-Gallego; Fernando Boisset; David A. Simpson (Kew Bulletin, 2016)

Long-term efavirenz use is associated with worse neurocognitive functioning in HIV-infected patients - Qing Ma; Florin Vaida; Jenna Wong; Chelsea A. Sanders; Yu-ting Kao; David Croteau; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; Justin C. McArthur; Susan Morgello; et al. (Journal of NeuroVirology, 2016)

Molecular tools for bathing water assessment in Europe: Balancing social science research with a rapidly developing environmental science evidence-base - David M. Oliver; Nick D. Hanley; Melanie van Niekerk; David Kay; A. Louise Heathwaite; Sharyl J. M. Rabinovici; Julie L. Kinzelman; Lora E. Fleming; Jonathan Porter; Sabina Shaikh; Rob Fish; Sue Chilton; et al. (Ambio, 2016)

Enigmatic spheres from the Upper Triassic Lockatong Formation, Newark Basin of eastern Pennsylvania: evidence for microbial activity in marginal-lacustrine strandline deposits - Edward L. Simpson; David L. Fillmore; Michael J. Szajna; Emily Bogner; Margariete G. Malenda; Kelsey M. Livingston; Brian Hartline (Palaeobiodiversity and Palaeoenvironments, 2015)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Challenges for using quantitative PCR test batteries as a TIE-type approach to identify metal exposure in benthic invertebrates - Sharon E. Hook; Hannah L. Osborn; David A. Spadaro; Stuart L. Simpson (Environmental Science and Pollution Research, 2015)

CSF biomarkers of monocyte activation and chemotaxis correlate with magnetic resonance spectroscopy metabolites during chronic HIV disease - Albert M. Anderson; Christine Fennema-Notestine; Anya Umlauf; Michael J. Taylor; David B. Clifford; Christina M. Marra; Ann C. Collier; Benjamin B. Gelman; Justin C. McArthur; J. Allen McCutchan; David M. Simpson; Susan Morgello; et al. (Journal of NeuroVirology, 2015)

Chemical characterization and in vitro toxicity of diesel exhaust particulate matter generated under varying conditions - Julie Richman Fox; David P. Cox; Bertram E. Drury; Timothy R. Gould; Terrance J. Kavanagh; Michael H. Paulsen; Lianne Sheppard; Christopher D. Simpson; James A. Stewart; Timothy V. Larson; Joel D. Kaufman (Air Quality, Atmosphere & Health, 2015)

Marine extinction risk shaped by trait–environment interactions over 500 million years - Emily A. Orzechowski; Rowan Lockwood; Jarrett E. K. Byrnes; Sean C. Anderson; Seth Finnegan; Zoe V. Finkel; Paul G. Harnik; David R. Lindberg; Lee Hsiang Liow; Heike K. Lotze; Craig R. McClain; Jenny L. McGuire; et al. (Global Change Biology, 2015)
Perhaps the most pressing issue in predicting biotic responses to present and future global change is understanding how environmental factors shape the relationship between ecological traits and extinction risk. The fossil record provides millions of years of insight into how extinction selectivity (i.e., differential extinction risk) is shaped by interactions between ecological traits and environmental conditions. Numerous paleontological studies have examined trait‐based extinction selectivity; however, the extent to which these patterns are shaped by environmental conditions is poorly understood due to a lack of quantitative synthesis across studies. We conducted a meta‐analysis of published studies on fossil marine bivalves and gastropods that span 458 million years to uncover how global environmental and geochemical changes covary with trait‐based extinction selectivity. We focused on geographic range size and life habit (i.e., infaunal vs. epifaunal), two of the most important and commonly examined predictors of extinction selectivity. We used geochemical proxies related to global climate, as well as indicators of ocean acidification, to infer average global environmental conditions. Life‐habit selectivity is weakly dependent on environmental conditions, with infaunal species relatively buffered from extinction during warmer climate states. In contrast, the odds of taxa with broad geographic ranges surviving an extinction (>2500 km for genera, >500 km for species) are on average three times greater than narrow‐ranging taxa (estimate of odds ratio: 2.8, 95% confidence interval = 2.3–3.5), regardless of the prevailing global environmental conditions. The environmental independence of geographic range size extinction selectivity emphasizes the critical role of geographic range size in setting conservation priorities.

Delayed mutual information infers patterns of synaptic connectivity in a proprioceptive neural network - Wagner Endo; Fernando P. Santos; David Simpson; Carlos D. Maciel; Philip L. Newland (Journal of Computational Neuroscience, 2015)

Nutritional ecology beyond the individual: a conceptual framework for integrating nutrition and social interactions - Mathieu Lihoreau; Camille Buhl; Michael A. Charleston; Gregory A. Sword; David Raubenheimer; Stephen J. Simpson (Ecology Letters, 2015)
Over recent years, modelling approaches from nutritional ecology (known as Nutritional Geometry) have been increasingly used to describe how animals and some other organisms select foods and eat them in appropriate amounts in order to maintain a balanced nutritional state maximising fitness. These nutritional strategies profoundly affect the physiology, behaviour and performance of individuals, which in turn impact their social interactions within groups and societies. Here, we present a conceptual framework to study the role of nutrition as a major ecological factor influencing the development and maintenance of social life. We first illustrate some of the mechanisms by which nutritional differences among individuals mediate social interactions in a broad range of species and ecological contexts. We then explain how studying individual‐ and collective‐level nutrition in a common conceptual framework derived from Nutritional Geometry can bring new fundamental insights into the mechanisms and evolution of social interactions, using a combination of simulation models and manipulative experiments.

Next-generation sequencing-based molecular diagnosis of 82 retinitis pigmentosa probands from Northern Ireland - Li Zhao; Feng Wang; Hui Wang; Yumei Li; Sharon Alexander; Keqing Wang; Colin E. Willoughby; Jacques E. Zaneveld; Lichun Jiang; Zachry T. Soens; Philip Earle; David Simpson; et al. (Human Genetics, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Cyperus beentjei, a new species of Cyperaceae from Tropical East Africa delimited through morphometric analysis - Lucinda R. Gardner; Odile Weber; David A. Simpson (Kew Bulletin, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Detecting Extinction Risk from Climate Change by IUCN Red List Criteria - DAVID A. KEITH; MICHAEL MAHONY; HARRY HINES; JANE ELITH; TRACEY J. REGAN; JOHN B. BAUMGARTNER; DAVID HUNTER; GEOFFREY W. HEARD; NICOLA J. MITCHELL; KIRSTEN M. PARRIS; TRENT PENMAN; BEN SCHEELE; et al. (Conservation Biology, 2014)
Anthropogenic climate change is a key threat to global biodiversity. To inform strategic actions aimed at conserving biodiversity as climate changes, conservation planners need early warning of the risks faced by different species. The IUCN Red List criteria for threatened species are widely acknowledged as useful risk assessment tools for informing conservation under constraints imposed by limited data. However, doubts have been expressed about the ability of the criteria to detect risks imposed by potentially slow‐acting threats such as climate change, particularly because criteria addressing rates of population decline are assessed over time scales as short as 10 years. We used spatially explicit stochastic population models and dynamic species distribution models projected to future climates to determine how long before extinction a species would become eligible for listing as threatened based on the IUCN Red List criteria. We focused on a short‐lived frog species (Assa darlingtoni) chosen specifically to represent potential weaknesses in the criteria to allow detailed consideration of the analytical issues and to develop an approach for wider application. The criteria were more sensitive to climate change than previously anticipated; lead times between initial listing in a threatened category and predicted extinction varied from 40 to 80 years, depending on data availability. We attributed this sensitivity primarily to the ensemble properties of the criteria that assess contrasting symptoms of extinction risk. Nevertheless, we recommend the robustness of the criteria warrants further investigation across species with contrasting life histories and patterns of decline. The adequacy of these lead times for early warning depends on practicalities of environmental policy and management, bureaucratic or political inertia, and the anticipated species response times to management actions. Detección del Riesgo de Extinción a partir del Cambio Climático por medio del Criterio de la Lista Roja de la UICNKeith et al.

Editorial - David A. Simpson; Ruth Linklater (Kew Bulletin, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Mechanisms driving an unusual latitudinal diversity gradient for grasses - Vernon Visser; W. Derek Clayton; David A. Simpson; Robert P. Freckleton; Colin P. Osborne (Global Ecology and Biogeography, 2014)
Aim For most higher‐order taxa, species diversity peaks sharply in the moist tropics and declines rapidly at higher latitudes. However, the mechanisms driving this latitudinal gradient are numerous, remain uncertain and are even undocumented in some important major clades such as the grasses. Grasses are a cosmopolitan, important plant family with more than 11,000 species world‐wide. Our aims were: to investigate the latitudinal distributions of species richness for different grass lineages, and the grass family as a whole; and to test hypotheses proposed in general for the latitudinal diversity gradient or specifically as determinants of grass species richness patterns at the global scale. Location Global. Methods We used the most comprehensive global database of grass distributions currently available to calculate species richness for 340 political regions of the world. Using generalized additive models we used these data to model the latitudinal gradients of species richness for different grass lineages and for the grass family as a whole. We constructed multiple regression models to include climatic, productivity, topographic, habitat and geographic variables. Results An unusual, shallow latitudinal diversity gradient arises because different grass lineages exhibit contrasting latitudinal patterns. This reflects differential specialization of grass lineages to arid and cool environments, the legacy of historical effects, most notably the Gondwanan origin of the grasses, and a strong association between grasses and topographically heterogeneous, mountainous regions. Main conclusions The grasses are one of the relatively few higher‐order lineages that exhibits an atypical latitudinal gradient; this has arisen because of climatic specialization of particular grass lineages to cold and arid environments. Key additional roles have been inferred for historical biogeography and topographical heterogeneity in determining global patterns of grass species richness. These mechanisms have generally been under‐appreciated and are probably important for many other lineages.

Latent cytomegalovirus infection and innate immune function following a 75 km cycling time trial - Emily C. P. LaVoy; David C. Nieman; Dru A. Henson; R. Andrew Shanely; Amy M. Knab; Lynn Cialdella-Kam; Richard J. Simpson (European Journal of Applied Physiology, 2013)

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Erratum to: Adaptive feedback analysis and control of programmable stimuli for assessment of cerebrovascular function - Lingke Fan; Glen Bush; Emmanuel Katsogridakis; David M. Simpson; Robert Allen; John Potter; Anthony A. Birch; Ronney B. Panerai (Medical & Biological Engineering & Computing, 2013)

Arthropod food webs become increasingly lipid‐limited at higher trophic levels - Shawn M. Wilder; Michael Norris; Raymond W. Lee; David Raubenheimer; Stephen J. Simpson (Ecology Letters, 2013)
Understanding why food chains are relatively short in length has been an area of research and debate for decades. We tested if progressive changes in the nutritional content of arthropods with trophic position limit the availability of a key nutrient, lipid, for carnivores. Arthropods at higher trophic levels had progressively less lipid and more protein in their bodies compared with arthropods at lower trophic levels. The nutrients present in arthropod bodies were directly related to the nutrients that predators extracted when feeding on those arthropods. As a consequence, nutrient assimilation shifted from lipid‐biased to protein‐biased as arthropods ascended trophic levels from herbivores to secondary carnivores. Successive changes in the nutritional consequences of predation may ultimately set an upper limit on the number of trophic levels in arthropod communities. Further work is needed to examine the influence of lipid and other nutrients on food web traits in a range of ecosystems.

Adaptive feedback analysis and control of programmable stimuli for assessment of cerebrovascular function - Lingke Fan; Glen Bush; Emmanuel Katsogridakis; David M. Simpson; Robert Allen; John Potter; Anthony A. Birch; Ronney B. Panerai (Medical & Biological Engineering & Computing, 2013)

Consistent proportional macronutrient intake selected by adult domestic cats (Felis catus) despite variations in macronutrient and moisture content of foods offered - Adrian K. Hewson-Hughes; Victoria L. Hewson-Hughes; Alison Colyer; Andrew T. Miller; Simon R. Hall; David Raubenheimer; Stephen J. Simpson (Journal of Comparative Physiology B, 2013)

Autonomic dysfunction is common in HIV and associated with distal symmetric polyneuropathy - Jessica Robinson-Papp; Sandeep Sharma; David M. Simpson; Susan Morgello (Journal of NeuroVirology, 2013)

A system identification analysis of neural adaptation dynamics and nonlinear responses in the local reflex control of locust hind limbs - Oliver P. Dewhirst; Natalia Angarita-Jaimes; David M. Simpson; Robert Allen; Philip L. Newland (Journal of Computational Neuroscience, 2013)

Connexin 26 facilitates gastrointestinal bacterial infection in vitro - Charlotte Simpson; David P. Kelsell; Olivier Marchès (Cell and Tissue Research, 2013)

Piper chantaranothaii (Piperaceae), a new species from Thailand - Chalermpol Suwanphakdee; David A. Simpson (Kew Bulletin, 2012)

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Neuromuscular complications in HIV: effects of aging - Jessica Robinson-Papp; Ik Lin Tan; David M. Simpson (Journal of NeuroVirology, 2012)

Above‐ and belowground responses of arctic tundra ecosystems to altered soil nutrients and mammalian herbivory - Laura Gough; John C. Moore; Gauis R. Shaver; Rodney T. Simpson; David R. Johnson (Ecology, 2012)
Theory and observation indicate that changes in the rate of primary production can alter the balance between the bottom‐up influences of plants and resources and the top‐down regulation of herbivores and predators on ecosystem structure and function. The Exploitation Ecosystem Hypothesis (EEH) posited that as aboveground net primary productivity (ANPP) increases, the additional biomass should support higher trophic levels. We developed an extension of EEH to include the impacts of increases in ANPP on belowground consumers in a similar manner as aboveground, but indirectly through changes in the allocation of photosynthate to roots. We tested our predictions for plants aboveground and for phytophagous nematodes and their predators belowground in two common arctic tundra plant communities subjected to 11 years of increased soil nutrient availability and/or exclusion of mammalian herbivores. The less productive dry heath (DH) community met the predictions of EEH aboveground, with the greatest ANPP and plant biomass in the fertilized plots protected from herbivory. A palatable grass increased in fertilized plots while dwarf evergreen shrubs and lichens declined. Belowground, phytophagous nematodes also responded as predicted, achieving greater biomass in the higher ANPP plots, whereas predator biomass tended to be lower in those same plots (although not significantly). In the higher productivity moist acidic tussock (MAT) community, aboveground responses were quite different. Herbivores stimulated ANPP and biomass in both ambient and enriched soil nutrient plots; maximum ANPP occurred in fertilized plots exposed to herbivory. Fertilized plots became dominated by dwarf birch (a deciduous shrub) and cloudberry (a perennial forb); under ambient conditions these two species coexist with sedges, evergreen dwarf shrubs, and Sphagnum mosses. Phytophagous nematodes did not respond significantly to changes in ANPP, although predator biomass was greatest in control plots. The contrasting results of these two arctic tundra plant communities suggest that the predictions of EEH may hold for very low ANPP communities, but that other factors, including competition and shifts in vegetation composition toward less palatable species, may confound predicted responses to changes in productivity in higher ANPP communities such as the MAT studied here.

The Bulbostylis capillaris complex (Cyperaceae) in southern South America - M. Gabriela López; David A. Simpson (Kew Bulletin, 2012)

Genetic features of cerebrospinal fluid-derived subtype B HIV-1 tat - Jun Yong Choi; George K. Hightower; Joseph K. Wong; Robert Heaton; Steven Woods; Igor Grant; Thomas D. Marcotte; Ronald J. Ellis; Scott L. Letendre; Ann C. Collier; Christina M. Marra; David B. Clifford; et al. (Journal of NeuroVirology, 2012)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

The role of cladocerans in tracking long-term change in shallow lake trophic status - Thomas A. Davidson; Helen Bennion; Erik Jeppesen; Gina H. Clarke; Carl D. Sayer; David Morley; Bent V. Odgaard; Peter Rasmussen; Ruth Rawcliffe; Jorge Salgado; Gavin L. Simpson; Susanne L. Amsinck (Hydrobiologia, 2011)

An Assessment of Three Harpacticoid Copepod Species for Use in Ecotoxicological Testing - Daniel J. Ward; Victor Perez-Landa; David A. Spadaro; Stuart L. Simpson; Dianne F. Jolley (Archives of Environmental Contamination and Toxicology, 2011)

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

A palaeolimnological meta-database for assessing the ecological status of lakes - Richard W. Battarbee; David Morley; Helen Bennion; Gavin L. Simpson; Michael Hughes; Viktorija Bauere (Journal of Paleolimnology, 2011)

Prey nutrient composition has different effects on Pardosa wolf spiders with dissimilar life histories - Kim Jensen; David Mayntz; Søren Toft; David Raubenheimer; Stephen J. Simpson (Oecologia, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Ice stream influence on West Greenland Ice Sheet dynamics during the Last Glacial Maximum - David H. Roberts; Antony J. Long; Bethan J. Davies; Matthew J. R. Simpson; Christoph Schnabel (Journal of Quaternary Science, 2010)
This paper investigates the processes governing bedrock bedform evolution in ice sheet and ice stream areas in central West Greenland, and explores the evidence for a cross‐shelf ice stream at the Last Glacial Maximum (LGM). To the east of Sisimiut the formation of streamlined bedforms with high elongation ratios and high bedform density has been controlled by geological structure and topography in slow‐flowing ice sheet areas. At the coast, the effects of regional flow convergence, caused by coastal fjord orientation, routed ice into the Sisimiut/Itilleq area where it formed an ice stream onset zone. This funnelled ice into an offshore trough (Holsteinsborg Dyb), resulting in a southwesterly regional ice flow direction and the formation of a topographically routed ice stream (Holsteinsborg Isbrae). To the south of this, striae and bedform evidence show that local valley glaciers initially flowed east to west across the coast, but were later redirected by the Itilleq Fjord ice which turned southwestward due to diffluent flow and deflection by Holsteinsborg Isbrae. Roches moutonnées in this area have low elongation ratios and high bedform density, but do not provide unequivocal support for ice streaming, as they are a product of both bedrock structure and changes in ice flow direction, rather than enhanced flow velocities. Cosmogenic surface exposure ages limit maximum ice sheet surface elevation to ca. 755–810 m above sea level in this region. Such ice thickness enabled Holsteinsborg Isbrae to reach the mid/outer continental shelf during the LGM, and to contribute to the formation of a trough mouth fan and the Outer Hellefisk moraines. Initial deglaciation across this region was driven by rising sea level and increasing air temperatures prior to the Bølling Interstadial at ca. 14.5 cal. ka BP. Between 12 and 10 cal. ka BP both increased air and ocean temperatures post the Younger Dryas, and peak sea‐level rise up to the marine limit, caused accelerated thinning and marginal retreat through calving, although dating evidence suggests ice streams remained along the inner shelf/coast boundary until at least ca. 10 cal. ka BP, their longevity maintained by increased ice thickness and ice discharge. Copyright © 2009 John Wiley & Sons, Ltd.

Peter Shaw Green (1920 – 2009) - David Simpson (Kew Bulletin, 2010)

Coleochloa domensis (Cyperaceae),a new epiphytic species from Cameroon - A. Muthama Muasya; Yvette Harvey; Martin Cheek; Kenneth Tah; David A. Simpson (Kew Bulletin, 2010)

Mnesithea thailandica a new species of Poaceae from Thailand - Paweena Traiperm; Thaweesakdi Boonkerd; Pranom Chantaranothai; David A. Simpson (Kew Bulletin, 2010)

Editorial - David Simpson; Ruth Linklater (Kew Bulletin, 2010)

Dietary ratio of protein to carbohydrate induces plastic responses in the gastrointestinal tract of mice - Allan Sørensen; David Mayntz; Stephen James Simpson; David Raubenheimer (Journal of Comparative Physiology B, 2010)

Editorial - David A. Simpson; Ruth Linklater (Kew Bulletin, 2009)

What is a Genus in Cypereae: Phylogeny, Character Homology Assessment and Generic Circumscription in Cypereae - A. Muthama Muasya; Alexander Vrijdaghs; David A. Simpson; Mark W. Chase; Paul Goetghebeur; Erik Smets (The Botanical Review, 2009)

Phylogeny of Cyperaceae Based on DNA Sequence Data: Current Progress and Future Prospects - A. Muthama Muasya; David A. Simpson; G. Anthony Verboom; Paul Goetghebeur; Robert F. C. Naczi; Mark W. Chase; Erik Smets (The Botanical Review, 2009)

Development of “universal” gene-specific markers from Malus spp. cDNA sequences, their mapping and use in synteny studies within Rosaceae - Daniel J. Sargent; Annalisa Marchese; David W. Simpson; Werner Howad; Felicidad Fernández-Fernández; Amparo Monfort; Pere Arús; Kate M. Evans; Kenneth R. Tobutt (Tree Genetics & Genomes, 2009)

Large-scale vulnerability assessments for natural hazards - David M. Simpson; R. Josh Human (Natural Hazards, 2008)

Uncertainties in the relationship between atmospheric nitrogen deposition and forest carbon sequestration - MARK A. SUTTON; DAVID SIMPSON; PETER E. LEVY; ROGNVALD I. SMITH; STEFAN REIS; MARCEL Van OIJEN; WIM De VRIES (Global Change Biology, 2008)
In a recent study, Magnani et al. report how atmospheric nitrogen deposition drives stand‐lifetime net ecosystem productivity (NEP av ) for midlatitude forests, with an extremely high C to N response (725 kg C kg −1 wet‐deposited N for their European sites). We present here a re‐analysis of these data, which suggests a much smaller C : N response for total N inputs. Accounting for dry, as well as wet N deposition reduces the C : N response to 177 : 1. However, if covariance with intersite climatological differences is accounted for, the actual C : N response in this dataset may be et al. Multisite regression of simulated NEP av vs. total N deposition reproduces a high C : N response (149 : 1). However, once the effects of intersite climatological differences are accounted for, the value is again found to be much smaller, pointing to a real C : N response of about 50–75 : 1.

Humidity parameters from temperature: test of a simple methodology for European conditions - Yvonne Andersson‐Sköld; David Simpson; Viel Ødegaard (International Journal of Climatology, 2008)
Atmospheric water content is important for local and regional climate, and for chemical processes of soluble and solute species in the atmosphere. Further, vapour pressure deficit ( D ) is one of the key controls on the opening of stomata in plants and is thus an important force for evapotransporation, plant respiration and biomass production and for the uptake of harmful pollutants such as ozone through the stomata. Most meteorological stations typically measure both temperature and relative humidity (RH). However, even if recorded at finer time resolution, it is usually the daily or often monthly means of RH which are published in climate reports. Unfortunately, such data cannot be used to obtain the changes in RH or vapour pressure deficit over the day, as this depends strongly on the diurnal temperature variation during the day and not upon the mean temperature. Although RH typically changes significantly over the day, the ambient vapour pressure is often remarkably constant. Here a simple method to estimate diurnal vapour pressure is evaluated, based upon an assumed constant vapour pressure, and that recorded minimum temperatures approximate dew‐point temperatures. With a knowledge of only temperature, we will show that day to day estimates of vapour pressure, humidity and especially D , can be made with reasonable accuracy. This methodology is tested using meteorological data from 32 sites covering a range of locations in Europe. Such a simple methodology may be used to extract approximate diurnal curves of vapour pressures from published meteorological data which contains only minimum temperatures for each day, or where humidity data are not available. Copyright © 2007 Royal Meteorological Society

Occurrence of Conchophthirus acuminatus (Protista: Ciliophora) in Dreissena polymorpha (Mollusca: Bivalvia) along the River Shannon, Ireland - David Bruce Conn; Sarah E. Simpson; Dan Minchin; Frances E. Lucy (Biological Invasions, 2008)

Chlorophyll fluorescence, root growth potential, and stomatal conductance as estimates of field performance potential in conifer seedlings - Sylvia J. L’Hirondelle; David G. Simpson; Wolfgang D. Binder (New Forests, 2007)

The Role of Cohort Studies in Drug Development: Clinical Evidence of Antiviral Activity of Serotonin Reuptake Inhibitors and HMG-CoA Reductase Inhibitors in the Central Nervous System - Scott L. Letendre; Jennifer Marquie-Beck; Ronald J. Ellis; Steven Paul Woods; Brookie Best; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina Marra; Justin C. McArthur; J. Allen McCutchan; Susan Morgello; et al. (Journal of Neuroimmune Pharmacology, 2007)

Overwinter Storability of Conifer Planting Stock: Operational Testing of Fall Frost Hardiness - Sylvia J. L’Hirondelle; David G. Simpson; Wolfgang D. Binder (New Forests, 2006)

Biogeography of wild Arachis (Leguminosae):distribution and environmental characterisation - Morag E. Ferguson; Andrew Jarvis; H. Tom Stalker; David E. Williams; Luigi Guarino; Jose F.M. Valls; Roy N. Pittman; Charles E. Simpson; Paula J. Bramel (Biodiversity and Conservation, 2005)

Clinical validation of the NeuroScreen - Ronald J Ellis; Scott R Evans; David B Clifford; Lauren R Moo; Justin C McArthur; Ann C Collier; Constance Benson; Ron Bosch; David Simpson; Constantin T Yiannoutsos; Yijun Yang; Kevin Robertson; et al. (Journal of NeuroVirology, 2005)

Heat shock protein 70 in the rat nasal cavity: localisation and response to hyperthermia - Sharon A. Simpson; David J. Alexander; Celia J. Reed (Archives of Toxicology, 2004)

Murine model of BCG lung infection: Dynamics of lymphocyte subpopulations in lung interstitium and tracheal lymph nodes - Rajiv K. Saxena; David Weissman; Janet Simpson; Daniel M. Lewis (Journal of Biosciences, 2002)

Plankton dynamics: observed and modelled responses to physical conditions in Prince William Sound, Alaska - David L. Eslinger; R. Ted Cooney; C. Peter Mcroy; Alison Ward; Thomas C. Kline; E. Paul Simpson; Jia Wang; Jennifer R. Allen (Fisheries Oceanography, 2001)
Plankton populations in Prince William Sound, Alaska, exhibited pronounced seasonal, annual and longer‐period variability in composition and standing stock in response to physically influenced differences in nutrient availability, and possibly currents that modify local biomass by exchanges with water from the bordering Gulf of Alaska. During springs in which early, strong physical stratification developed, intense, short‐lived phytoplankton blooms occurred. These blooms had relatively short residence times in the water column. In contrast, during springs in which slower, weaker stratification developed, phytoplankton blooms were prolonged and took longer to peak. These slower blooms prolonged the period of phytoplankton production, prolonged interaction with the springtime grazing community and led to the incorporation of more organic matter into pelagic food webs. A coupled biological‐physical simulation of plankton production was used to examine the implications of seasonally varying air and mixed‐layer temperatures, surface winds and incident light on the timing, duration, annual production and standing stock of plankton. Our modelling results reproduced the observed characteristics of the springtime production cycle, and the magnitude of zooplankton stocks for the period 1992–97 but not for 1981–91. These results suggest that for most of the 1990s, bottom‐up influences on nutrient supplies controlled levels of primary consumers, whereas for the 11 years before that, other unknown factors dominated this process. We present the results of a comprehensive, multiyear study of relationships between plankton and physical limitations, and a retrospective analysis of earlier conditions to explore the possible causes for these differences.

Phytoplankton distribution and survival in the thermocline - Jonathan Sharples; Mark C. Moore; Tom P. Rippeth; Patrick M. Holligan; David J. Hydes; Neil R. Fisher; John H. Simpson (Limnology and Oceanography, 2001)
Observations of the vertical structure of density, concentrations of chlorophyll a and nitrate, and turbulent dissipation rates were made over a period of 25 h in a well‐stratified shelf region in the Western English Channel, between neap and spring tides. Maximum turbulent dissipation at the base of the thermocline occurred almost 5 h after maximum tidal currents. This turbulence aids phytoplankton growth by supplying bottom‐layer nutrients into the subsurface chlorophyll maximum but reduces phytoplankton concentrations in the thermocline by mixing cells from the base of the subsurface maximum into the bottom mixed layer. The turbulent dissipation observations were used to estimate an average nitrate flux into the thermocline of 2.0 (0.8‐3.2, 95% confidence interval) mmol m −2 d −1 , which is estimated to have been capable of supporting new phytoplankton growth at a rate of 160 (64–256) mg C m −2 d −1 . Turbulent entrainment of carbon from the base of the subsurface biomass maximum into the bottom mixed layer was observed to be 290 (120–480) mg C m −2 d −1 . This apparent excess export from the chlorophyll maximum is suggested to be a feature of the spring‐neap cycle, with export dominating as the tidal turbulence increases toward spring tides and erodes the base of the thermocline. The observed rate of carbon export into the bottom mixed layer could account for as much as 25% of the gross annual primary production in stratifying shelf seas. Such turbulent losses, combined with grazing losses and low light levels, suggest that phytoplankton need to be highly adapted to environmental conditions within the thermocline in order to survive.

A Parametric Approach to Measuring Cerebral Blood Flow Autoregulation from Spontaneous Variations in Blood Pressure - David M. Simpson; Ronney B. Panerai; David H. Evans; A. Ross Naylor (Annals of Biomedical Engineering, 2001)

Ultrasound for the Visualization and Quantification of Tumor Microcirculation - F. Stuart Foster; Peter N. Burns; David H. Simpson; Stephanie R. Wilson; Donald A. Christopher; David E. Goertz (Cancer and Metastasis Reviews, 2000)

Objective Response Detection in an Electroencephalogram During Somatosensory Stimulation - David M. Simpson; Carlos J. Tierra-Criollo; Renato T. Leite; Eduardo J. B. Zayen; Antonio F. C. Infantosi (Annals of Biomedical Engineering, 2000)

Organophosphate neuropathy due to methamidophos: biochemical and neurophysiological markers - Rob McConnell; Edgar Delgado-Téllez; Ricardo Cuadra; Edmundo Tórres; Matthew Keifer; Juan Almendárez; Jamilet Miranda; Hassan A. N. El-Fawal; Mary Wolff; David Simpson; Ingvar Lundberg (Archives of Toxicology, 1999)

The ferric-reducing activity of duodenal brush-border membrane vesicles is associated with a b-type haem - David J. Pountney; Kishor B. Raja; Robert J. Simpson<; John M. Wrigglesworth (BioMetals, 1999)

Biochemical and biophysical analysis of the intracellular lipid binding proteins of adipocytes - Melanie A. Simpson; Vince J. LiCata; Natalie Ribarik Coe; David A. Bernlohr (Molecular and Cellular Biochemistry, 1999)

A cysteine endopeptidase with a C-terminal KDEL motif isolated from castor bean endosperm is a marker enzyme for the ricinosome, a putative lytic compartment - Markus Schmid; David Simpson; Frantisek Kalousek; Christine Gietl (Planta, 1998)

Gaseous and Particulate Oxidized and Reduced Nitrogen Species in the Atmospheric Boundary Layer in Scandinavia in Spring - Asgeir Sorteberg; Øystein Hov; Sverre Solberg; Kjetil Tørseth; Hans Areskoug; Martin Ferm; Kit Granby; Heikki Lättilä; Karin Persson; David Simpson (Journal of Atmospheric Chemistry, 1998)

Changes in the levels of seven proteins involved in polypeptide folding and transport during endosperm development of two barley genotypes differing in storage protein localisation - Søren Møgelsvang; David J. Simpson (Plant Molecular Biology, 1998)

An assessment of suprageneric phylogeny inCyperaceae usingrbcL DNA sequences - Abraham M. Muasya; David A. Simpson; Mark W. Chase; Alastair Culham (Plant Systematics and Evolution, 1998)

European VOC Emission Estimates Evaluated by Measurements and Model Calculations - øystein Hov; Asgeir Sorteberg; Norbert Schmidbauer; Sverre Solberg; Frode Stordal; David Simpson; Anne Lindskog; Hans Areskoug; Pedro Oyola; Heikki Lättilä; Niels Z. Heidam (Journal of Atmospheric Chemistry, 1997)

An expanded collection of mouse Y Chromosome RDA clones - David E. Bergstrom; Hailing Yan; Manjula M. Sonti; Sandya Narayanswami; Janet K. Bayleran; Elizabeth M. Simpson (Mammalian Genome, 1997)

Does RGP predict field performance? A debate - David G. Simpson; Gary A. Ritchie (New Forests, 1997)

Ecological-economic modelling of the conservation of threatened habitats: heather moorland in the Northern Isles of Scotland - Nick Hanley; Hilary Kirkpatrick; Ian Simpson; David Oglethorpe; Angus Macdonald (Biodiversity and Conservation, 1996)